Visual Outcomes of Keratoprosthesis Versus Keratoplasty in Infective and Degenerative Corneal Opacifying Disorders - Fareeha Mirza, Sidrah Latif, Anaam Rehman, Fakhar Humayun, Tariq Pervaiz Khan, Muhammad Imran Ali, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Infective and degenerative corneal opacities compromise visual acuity and pose therapeuticchallenges. This experimental comparative study evaluated visual outcomes of keratoprosthesis